(untitled) (The Research of Medical Science Review, 2025)
Introduction: Gestational diabetes mellitus (GDM) is a common pregnancy complication associated with adverse maternal and fetal outcomes. Vitamin B12 deficiency has been linked to insulin resistance and metabolic dysfunction, but its association with GDM remains unclear. This study aimed to evaluate the relationship between vitamin B12 deficiency and GDM in pregnant women. Methodology: A case-control study was conducted at the Department of Obstetrics & Gynecology, National Hospital, Lahore, over six months. A total of 60 pregnant women (>24 weeks gestation) were enrolled, with 30 cases (GDM) and 30 controls (non-GDM). Vitamin B12 levels were assessed, and deficiency was defined as <150 pg/ml. Data were analyzed using SPSS, with odds ratios (OR) and p-values calculated to determine associations. Results: Vitamin B12 deficiency was significantly higher in GDM cases (40.0%) compared to controls (13.3%) (p = 0.020, OR = 4.333). The mean vitamin B12 level was lower in cases (196.01±66.61 pg/ml) than in controls (219.09±50.39 pg/ml) (p = 0.001). Conclusion: Vitamin B12 deficiency was significantly associated with GDM, with a higher prevalence in younger, primiparous women and those lacking folic acid intake. These findings highlight the need for early screening and nutritional interventions to prevent B12 deficiency in pregnant women at risk of GDM.